Synthesis and characterization of superabsorbent carbonaceous coated nitrogen phosphorus potassium (NPK) fertilizer - Norlirabiatuladawiyah, Che Ani (2018)
The aimed of this work is to produce CRWR fertilizer coated by superabsorbent carbonaceous polymer (SAC). In order to achieve to main objective, the work has been classified into three stages; synthesizing of the carbonaceous fibers material from the natural kenaf fibers, producing the superabsorbent carbonaceous fibers materials and NPK compound by coating process and investigating the behavior of the superabsorbent carbonaceous fiber polymer coated NPK compound through the controlled-release and water-retention properties. Initially, a study of the conversion of natural kenaf fiber to carbonaceous fiber through hydrothermal process was conducted at different operating time (2h-14h). The purpose of this study is to identify the highest carbon content and carbonaceous fiber at 6 hours operating time was selected to use as filler in the production of SAC polymer. Then, the study was continued on the graft polymerization of acrylic acid to produce superabsorbent polymer (SAP) by varying the amount of cross-linker was investigated. The effect at different amount of cross-linker in synthesized superabsorbent polymers (SAP) was identified in terms of water absorbency responses. The optimum properties of SAP were used in production of superabsorbent carbonaceous (SAC) polymer at different amount of carbonaceous fiber. Afterward, the optimum water absorbency of synthesize SAP and SAC polymer were characterized using tea-bag method in deionize water. The structures of synthesize SAP and SAC polymer were characterized by Fourier Transform Infrared Spectroscopy (FTIR) and morphologies were examined by Scanning Electron Microscope (SEM) testing. The optimum result of water absorbency of SAP (170.11 g water/g sample) at MBA0.01. Then, the high water absorbency of SAC polymer was recorded (293 g water/g sample) at MBA0.01-C2.0. The CRWR fertilizer that was produced was analyzed for controlled-release and water retention (CRWR) and water retention (WR) in soil analyses for 30 days. The releasing nutrients of nitrogen (N), phosphorus (P) and potassium (K) elements were tested by Induced Coupled Plasma-Mass Spectrometry (ICP-MS) analyzer. Analysis from CRWR and WR in soil proved that NPK fertilizer coating by SAC polymer could enhance the soil absorption and water holding capacity. Meanwhile, the releasing of nutrients from the coated layer was recorded slowly and consistent release compared to NPK fertilizer. Then, kinetic study was calculated from CRWR analysis to identify the release mechanism of nutrients in soil by using Korsmeyer-Peppas model. The nutrients release mechanism for all samples following Fickian diffusion controlled released since the value of n in between 0.5 to 1.0. Other than that, NPK fertilizer coated by SAC polymer fitted well with Korsmeyer-Peppas model since the value of r2 was in range 0.95 to 0.99. The diffusion coefficient of NPK fertilizer coated by SAC polymer was the highest compared to NPK fertilizer coated by SAP.